Activins and Follistatin in Chronic Hepatitis C and Its Treatment with Pegylated-Interferon-α Based Therapy. (19th April 2015) - Refaat, Bassem; Ashshi, Ahmed Mohamed; El-Shemi, Adel Galal; Azhar, Esam
Abstract : Pegylated-interferon- α based therapy for the treatment of chronic hepatitis C (CHC) is considered suboptimal as not all patients respond to the treatment and it is associated with several side effects that could lead to dose reduction and/or termination of therapy. The currently used markers to monitor the response to treatment are based on viral kinetics and their performance in the prediction of treatment outcome is moderate and does not combine accuracy and their values have several limitations. Hence, the development of new sensitive and specific predictor markers could provide a useful tool for the clinicians and healthcare providers, especially in the new era of interferon-free therapy, for the classification of patients according to their response to the standard therapy and only subscribing the novel directly acting antiviral drugs to those who are anticipated not to respond to the conventional therapy and/or have absolute contraindications for its use. The importance of activins and follistatin in the regulation of immune system, liver biology, and pathology has recently emerged. This review appraises the up-to-date knowledge regarding the role of activins and follistatin in liver biology and immune system and their role in the pathophysiology of CHC.